A Third-Year Medical School Ophthalmology Curriculum for a Longitudinal Integrated Clerkship Model - A. Itzam Marin; Helio Neves da Silva; Hongan Chen; Nihaal Mehta; Linh K. Nguyen; Jeffrey R. SooHoo; Jennifer E. Adams; Jasleen K. Singh (Journal of Academic Ophthalmology, 2022)
Background Longitudinal Integrated Clerkships (LICs) are innovative educational models that allow medical student continuity with patients, preceptors, colleagues, and health care systems. Given their benefits, the number of LICs continues to increase. We share a pilot model for an ophthalmology LIC curriculum at the University of Colorado School of Medicine targeted for students to see patients through transitions of care. Methods A needs assessment was performed including literature search, interviews with expert faculty, and a precurricular student questionnaire. Based on our findings, we developed a pilot two-part curriculum consisting of an introductory lecture and a half-day clinical experience designed to integrate patient eye care into the LIC model. At the end of the year, students completed a questionnaire assessing attitude, confidence, and knowledge. Precourse data were collected from students in the academic year (AY) 2018/2019 to aid with the needs assessment. Postcourse data were collected after completion of the curriculum from students in AY 2019/2020. Data from questionnaire were intended to improve our curricular experience. Results Our curriculum was piloted between the 2019 and 2020 AY. The completion rate of our curriculum was 100%. The questionnaire response rate was 90% in pre- and postcurricular groups (n=15/17 and n=9/10, respectively). Hundred percent of students from both groups responded that it is “very important”/“important” for all physicians to be able to identify when ophthalmology referral is indicated. After the intervention, there were significant differences in the rate of students responding that they were “confident” diagnosing acute angle-closure glaucoma (36 vs. 78%, p=0.04), treating a chemical burn (20 vs 67%, p=0.02), and diagnosing viral conjunctivitis (27 vs. 67%); 90% of students reported increased confidence in longitudinal care of patients in the eye clinic. Conclusions Medical students believe in the importance of ophthalmic education regardless of their specialty of choice. We present a pilot model to introduce ophthalmology within an LIC model. Future studies with a larger sample are needed to determine the impact of this model in terms of knowledge acquisition and relationship between curriculum and ophthalmology interest among students. Our curriculum can be adapted to other underrepresented specialties in the medical school curriculum and is easily exportable to other LICs.